Multi-fidelity algorithms for interactive mobile applications - Satyanarayanan, M.; Narayanan, Dushyanth (Wirel. Netw., 2001)
We introduce the concept of multi-fidelity algorithms, which revises the classical notion of an algorithm. Instead of having a fixed output criterion and allowing the resource consumption to vary, we bound the resource consumption and allow the fidelity or output criterion to vary. We discuss how multi-fidelity algorithms can improve the latency and battery life of interactive mobile applications. An extension of this idea allows the system to automatically discover sweet spots: sharp discontinuities in the fidelity-resource tradeoff space.